The change-in-stage and updated smoking status results from a cluster-randomized trial of smoking prevention and cessation using the transtheoretical model among British adolescents. - Aveyard, P; Sherratt, E; Almond, J; Lawrence, T; Lancashire, R; Griffin, C; Cheng, K (2001)
BACKGROUND: The transtheoretical model (TTM) and computer technology are promising technologies for changing health behavior, but there is little evidence of their effectiveness among adolescents. METHOD: Four thousand two hundred twenty-seven Year 9 (ages 13-14) pupils in 26 schools were randomly allocated to control and 4,125 in 26 schools were allocated to TTM intervention. TTM pupils received three whole class lessons and three sessions with an interactive computer program. Control pupils received no special intervention. Positive change in stage and smoking status was assessed from a questionnaire completed at baseline, 1 year, and 2 years. Random effects logistic regression was used to compare the change in stage and smoking status between the arms. RESULTS: Eighty-nine percent of the TTM group and 89.3% of the control group were present at 1-year and 86.0 and 83.1%, respectively, were present at 2-year follow-up. The adjusted odds ratio (95% confidence interval) for positive stage movement in the TTM relative to control was 1.13 (0.91-1.41) at 1 year and 1.25 (0.95-1.64) at 2 years and for regular smoking was 1.14 (0.93-1.39) at 1 year and 1.06 (0.86-1.31) at 2 years. Subgroup analysis by initial smoking status revealed no benefit for prevention or cessation. CONCLUSIONS: The intervention was ineffective.